Pembelajaran team games tournament menggunakan permainan tradisional gatrik untuk meningkatkan profil gotong royong dan koneksi matematis - Yuda, Erlangga Kusuma; Hendrayana, Aan; Rosmilawati, Ila (IKIP Siliwangi, 2025)
Many students struggle to understand length measurement, especially when solving real-life story problems. This reflects weak mathematical connection skills. Furthermore, students’ reluctance to collaborate with peers indicates a low cooperative learning profile. To address this issue, this study examines the impact of the Team Games Tournament (TGT) cooperative learning model, supported by the traditional game gatrik, on students’ mathematical connection skills and cooperation profile. A sequential explanatory mixed-method approach was used. Data were collected through tests, questionnaires, observations, and interviews. Quantitative data were analyzed using t-tests, while qualitative data were examined using Miles and Huberman’s interactive model, combined with Yin’s time series analysis. The results show that the TGT model with gatrik significantly improves both mathematical connection skills and cooperative behavior. This study provides insights for teachers to strengthen students’ mathematical and social competencies and serves as a reference for future research on cooperative learning and contextual media in education.